New approaches to diagnosis and management of patients with metabolic-associated steatotic liver disease with immune response to SARS-CоV-2 - V.I. Didenko; S.L. Melanich; I.A. Klenina; O.M. Tatarchuk; O.P. Petishko; H.I. Bocharov (Gastroenterologìa)
Background. The detrimental interaction of complex inflammatory pathways, which are chronically present in metabolic-associated steatotic liver disease (MASLD), can be dramatically exacerbated in the setting of COVID-19, contributing to the development of liver fibrosis. To date, there is no consensus on the use of serum parameters instead of liver biopsy as criteria for predicting the unfavorable course of MASLD in patients with an immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The purpose of the study was to optimize the diagnosis and management of patients with MASLD and an immune response to SARS-CoV-2 by identifying predictors of adverse outcome. Materials and methods. The study included 105 patients with MASLD who had an elevated level of IgG antibodies specific to SARS-CoV-2 of more than 40 BAU/ml compared to the control value, which allowed us to conclude that these patients had an immune response. The stiffness of the liver parenchyma was assessed by shear wave elastography (SWE) using an expert-class ultrasound scanner Soneus P7 (Ultrasign, Ukraine, Switzerland). All patients’ serum parameters of immunological profile, liver function, and prothrombotic environment were determined. The results were statistically analyzed using the Statistica 10 software package. Results. According to the results of SWE, 49 (46.7 %) patients had no liver fibrosis, 40 (38.1 %) were diagnosed with mild fibrosis (5.79–7.5 kPa) with an average value of (6.08 ± 0.13) kPa, and 16 (15.2 %) had moderate fibrosis (7.5–10.0 kPa) with an average value of (7.65 ± 0.38) kPa. In patients with unfavorable course of MASLD, the level of aspartate aminotransferase was (50.1 ± 14.9) U/L and was 2 times higher than in the control group — (23.4 ± 10.3) U/L (p < 0.001) and in patients without liver fibrosis — (27.0 ± 9.1) U/L (p < 0.001). In the development of unfavorable course of MASLD in patients with an immune response to SARS-CoV-2, the mean platelet volume increased by 11 % (p < 0.001) compared to the controls and group without liver fibrosis. Similar changes were found when assessing the absolute number of CD16+, namely, in patients with unfavorable course of MASLD, this indicator was (0.42 ± 0.15) · 109 c/L, which is 45 % higher than in the control group — (0.29 ± 0.21) · 109 c/L (p < 0.001) and 40 % higher than in patients without liver fibrosis — (0.30 ± 0.09) · 109 c/L (p < 0.001). In patients with MASLD and an immune response to SARS-CoV-2, the most significant correlations of liver parenchymal stiffness (based on SWE data) were observed with the absolute number of CD16+ cells (r = 0.568; p < 0.0001), aspartate aminotransferase levels (r = 0.503; p = 0.0001), and mean platelet volume (r = 0.513; p = 0.0001). According to the results of logistic regression analysis, the threshold values of predictors for adverse course of MASLD in patients with an immune response to SARS-CoV-2 were determined: absolute number of CD16+ more than 0.35 (sensitivity 82.1 %, specificity 92.9 %), aspartate aminotransferase level above 49 U/L (sensitivity 71.4 %, specificity 96.4 %) and MPV more than 8.5 fL (sensitivity 89.3 %, specificity 67.9 %). Conclusions. The management of patients with MASLD and an immune response to SARS-CoV-2 should include an assessment of the risk of adverse course of MASLD, which will allow for timely application of preventive and therapeutic measures to prevent the development of severe liver fibrosis and improve the quality of life of patients.